Dissolution of cholesterol gall stones using methyltertbutyl ether: a safe effective treatment. - McNulty, J (1991)
Methyltertbutyl ether (MTBE) administered by percutaneous transhepatic catheter rapidly dissolves radiolucent cholesterol gall bladder stones. However, complete dissolution and clearance of non-cholesterol debris is essential to prevent recurrence. In this study we analysed 25 consecutive patients with reference to efficacy and recurrence based on the presence or absence of non-cholesterol stone fragments after dissolution. Placement of the catheter was successful in 24 patients, one patient requiring cholecystectomy for bile peritonitis. MTBE was infused and aspirated continuously, four to six cycles per minute, resulting in rapid stone dissolution (median six hours; range 4-23 hours for solitary stones and median seven hours, range 4-30 hours for multiple stones). In 18 patients who had complete dissolution, four (22%) had recurrent stones within six to 18 months. Five patients had residual debris which failed to clear completely despite bile acid treatment. One patient with an incomplete rim of calcium in a large stone did not respond to MTBE treatment. A further patient required cholecystectomy for symptomatic recurrence. There were no serious side effects observed. MTBE treatment is a rapid, safe, and effective treatment for patients who refuse surgery or who for medical reasons cannot undergo cholecystectomy. The results of this study confirm that complete dissolution of all fragments is essential and may prevent recurrence.